PENGARUH KONSENTRASI KMnO4 TERHADAP BIOLEKTRISITAS DOUBLE CHAMBER MICROBIAL FUEL CELL DENGAN SUBTRAT LIMBAH KULIT KAKAO - Fitriana, Fitriana; Auliq, Muhammad A'an; Galuh, Senki Desta; Sutikno, Sutikno; Adytia, Daffa Gibran; Hasan, Moh. Ibnu (Jurnal Media Elektro, 2025)
The increasing use of fossil fuels for electricity generation leads to scarcity and greenhouse gas emissions, necessitating a solution in the form of a transition to environmentally friendly renewable energy. One renewable energy source that is currently being developed is the Microbial Fuel Cell (MFC), which utilizes bacterial metabolism to generate electrical energy. MFC generally consists of two chambers: an anode chamber containing microorganisms and substrates, and a cathode chamber containing an electrolyte solution. The organic material used as a substrate in the anode chamber of the MFC in this study is cocoa pod husk waste, while the electrolyte solution in the cathode chamber is potassium permanganate (KMnO₄). This study will analyze the effect of KMnO₄ concentration on the bioelectricity of the cocoa pod husk MFC, including current, voltage, and power density. The KMnO₄ concentrations used are 0.02 M, 0.03 M, and 0.04 M. The bioelectricity testing results show that the KMnO₄ concentration in the cathode chamber affects the system's performance, with a 0.03 M concentration producing the highest current and power density.